Comparison of the left ventricle mass variability calculated from echocardiography, traditional and averaged electrocardiography in the evaluation of the effectiveness of antihypertensive therapy - A. A. Semenkin; O. I. Chindareva; N. V. Makhrova; G. I. Nechaeva; V. V. Potapov; L. A. Zhivilova; I. E. Sivkov; E. V. Semenova (Лечащий Врач, 2021)
The comparison of the variability of left ventricular mass (LVM) calculated from echocardiography, conventional and signalaveraged ECG and evaluation the effectiveness of these methods in the detection of the LVM changes during antihypertensive therapy were performed. It was found that the reproducibility of the signal-averaged ECG method of LVM calculation is significantly higher than the conventional one and echocardiography. The use of this method in clinical practice can provide reliability of individualized assessment of LVM changes on single examination and during follow-up. The use of signal-averaged ECG may reduce groups size or the study duration to achieve statistically significant difference in studies with ECG control.